THE INFLUENCE OF PRODUCT QUALITY, SERVICE QUALITY AND LOCATION ON CUSTOMER SATISFACTION FOR BAKSO PAK NASIR CITA HATI SURABAYA - Mira Gayatri Kartika; Dyah Pelitawati; Walimatul Chasanah (WORLDVIEW ( Development economic and sharia studies journal ), 2023)
This study aims to analyze and determine the effect of product quality, service quality and location on customer satisfaction of Bakso Pak Nasir Cita Hati Surabaya. The data collection method used is questionnaire data. With population and samples are consumers of Bakso Pak Nasir Cita Hati Surabaya, totaling 75 respondents. The instrument in this study used a Likert scale and the technique used was Non-Probability Sampling technique with an Accidental Sampling approach. By using the formula Hair et al. The data analysis method used is multiple linear regression analysis using the SPSS version 23.0 statistical test tool. The results showed that the tcount of the Product Quality variable was 3.366 with a ttable value of 0.2272 and Sig obtained a sig of 0.000 <0.05, the tcount of the Service Quality variable was 3.112 with a ttable value of 0.667 and Sig obtained a result of 0.000 <0.05, the Location tcount was 3.36 with a ttable value of 0.667 and Sig obtained a result of 0.000 <0.05. So it can be said that the Poduk Quality, Service Quality, Location Variables simultaneously have a significant effect on Customer Satisfaction at Bakso Pak Nasir Cita Hati Surabaya. While the R Square test is obtained at 0.656 or 65.6% of the independent variables, namely Product Quality, Service Quality and Location, affect the dependent variable, namely Customer Satisfaction. And the remaining 34.4% is influenced by other factors.